2012
DOI: 10.1111/j.1365-2648.2012.05988.x
|View full text |Cite
|
Sign up to set email alerts
|

An open trial of self‐help behaviours of clients with eating disorders in an online programme

Abstract: Internet-based self-help programmes for eating disorders are helpful adjuncts to professional treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
1
28
0
1
Order By: Relevance
“…It is important to investigate the acceptability of internet‐based treatments for ED, meaning how well individuals with an ED accept internet‐based treatments. Overall, such treatments appear to be highly acceptable . Participants indicated that the treatments were useful and pleasant, and easy to use.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to investigate the acceptability of internet‐based treatments for ED, meaning how well individuals with an ED accept internet‐based treatments. Overall, such treatments appear to be highly acceptable . Participants indicated that the treatments were useful and pleasant, and easy to use.…”
Section: Resultsmentioning
confidence: 99%
“…Three other studies reported on cognitive behavioral therapy (CBT) delivered via e‐mail, hereafter referred to as e‐mail therapy. One study investigated a cognitive behavioral self‐help program with internet‐based guidance and another study investigated an open trial of internet‐based unguided self‐help . The majority of the included studies ( N = 14) reported on internet‐based CBT.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen studies (83%) examined programs which the authors reported to be CBT‐based. Five studies did not use CBT as their primary intervention and described using a mix of psychoeducation, self‐monitoring and motivational interviewing (Aardoom et al, ; Cardi et al, ; Hötzel et al, ; Leung et al, ; Strandskov et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of contact was reported as once per week across all studies, apart from two studies, which provided guidance one to two times per week (ter Huurne et al, ; ter Huurne et al, ). Two studies (Bara‐Carril et al, ; Leung et al, ) did not provide any support or guidance for participants, neither via a technological platform nor face‐to‐face. For further details regarding the nature of clinician support in each study, see Table .…”
Section: Resultsmentioning
confidence: 99%